Pemberdayaan Masyarakat Inovatif dalam Mendukung Kemajuan Daerah Perkotaan - Yulius Christian (Inovbook, 2021)
The development of the world today has been moving so fast, technology has made the boundaries between information and human needs closer. This speed and accuracy is also needed in the process of government and citizen interaction, but unfortunately the high mobility of citizens is not matched by the accuracy and speed of the government in terms of services, especially services to the public. This study aims to analyze innovation as a way to empower people to play an active role in the progress of urban areas. This research uses a descriptive qualitative method that describes an objective state or certain event based on visible facts or as it should be, which is then accompanied by general conclusions based on these historical facts. The population in this study are cities that have made innovations in their regions, while the samples in this study are innovations carried out by Bontang City, Palembang City and Makassar City which aim to empower the community to play an active role in helping realize the progress of their region. The results of this research prove that innovation is the transformation of knowledge into new products, processes and services, the act of using something new. Where innovation is the successful exploitation of a new idea or in other words is the mobilization of knowledge, technological skills and experience to create new products, processes and services. Palembang City and Makassar City which aim to empower the community to play an active role in helping to realize the progress of their regions. The results of this research prove that innovation is the transformation of knowledge into new products, processes and services, the act of using something new. Where innovation is the successful exploitation of a new idea or in other words is the mobilization of knowledge, technological skills and experience to create new products, processes and services. Palembang City and Makassar City which aim to empower the community to play an active role in helping to realize the progress of their regions. The results of this research prove that innovation is the transformation of knowledge into new products, processes and services, the act of using something new. Where innovation is the successful exploitation of a new idea or in other words is the mobilization of knowledge, technological skills and experience to create new products, processes and services.